A macrorealistic test in hybrid quantum optomechanics. (9th March 2020) - Marchese, Marta; McAleese, Hannah; Bassi, Angelo; Paternostro, Mauro
Abstract: We discuss a scheme for macrorealistic theories of the Leggett–Garg form (Leggett and Garg 1985 Phys. Rev. Lett. 54 857). Our scheme is based on a hybrid optomechanical system. It seems reasonable to test these inequalities with an optomechanical system, since in an optomechanical cavity it is possible to create non-classical states of the mirror through a projective measurement on the cavity field. We will present the protocol to generate such non-classicality for a general optomechanical cavity and after we will carry out a theoretical test for one of the possible formulations of these inequalities using a hybrid optomechanical system. Specifically, the inequality will be investigated for an harmonic oscillator coupled to a two-level system, which replaces the light field of the cavity. The aim is to reproduce, with this system, the evolution of a single spin-1/2 for which the inequality is violated; this is achievable through the conditioning of the two-level system which will be used as an ancilla.